2018
DOI: 10.1111/mms.12552
|View full text |Cite
|
Sign up to set email alerts
|

Harbor porpoise (Phocoena phocoena) reactions to pingers

Abstract: The use of acoustic alarms (pingers) has been mandated in several gill net fisheries around the world. Even though pingers have shown to reduce the incidental catch there are still questions to be answered in relation to effective range, habituation and displacement. In the present studies, the vocalization behavior of porpoises was recorded in response to two different pingers, AQUAmark100 (20–160 kHz) and AQUAmark300 (10 kHz). The Scottish experiment included an AQUAmark100 pinger running in on/off cycles. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…This might suggest that porpoises were not distributed differently on the inshore and offshore side of the experimental pinger station, respectively. Kindt‐Larsen et al (2019) logged porpoise click trains using T‐PODS anchored at different distances from Aquamark 100 and Aquamark 300 pingers, with a similar experimental setup. Their study found that the distribution of porpoises might have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…This might suggest that porpoises were not distributed differently on the inshore and offshore side of the experimental pinger station, respectively. Kindt‐Larsen et al (2019) logged porpoise click trains using T‐PODS anchored at different distances from Aquamark 100 and Aquamark 300 pingers, with a similar experimental setup. Their study found that the distribution of porpoises might have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…Fishing hooks equipped with different types of magnets (neodymium-iron-boron or barium-ferrite) have been successful at catching fewer elasmobranch species compared to control fishing hooks without magnets, showing promise for the potential decrease of fishing bycatch (O'Connell et al 2011b). Sound has shown promise in deterring cetaceans (Culik et al 2001;Kindt-Larsen et al 2019), and teleosts (Kastelein et al 2007) but much more research needs to be done on elasmobranchs in a field setting to determine the potential of acoustic cues in bycatch avoidance (Jordan et al 2013;Ryan et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the fact that clicks are produced almost continuously and that animals are constantly moving around has made PAM a very important tool for studying this species in the field. It is also widely used to successfully assess the impact on porpoises from many man-made activities, such as noise from coastal wind farms 1 , 16 19 and deterrent signals intended to keep them away from gill nets 20 – 24 .…”
Section: Introductionmentioning
confidence: 99%